Are We Asking Too Much of the Health Sector? Exploring the Readiness of Brazilian Primary Healthcare to Respond to Domestic Violence Against Women - Ana Flávia Pires Lucas d'Oliveira; Stephanie Pereira; Loraine J. Bacchus; Gene Feder; Lilia Blima Schraiber; Janaina Marques de Aguiar; Renata Granusso Bonin; Cecilia Guida Vieira Graglia; Manuela Colombini (Kerman University of Medical Sciences, 2022)
BackgroundThere is growing recognition of the health sector's potential role in addressing domestic violence (DV) against women. Although Brazil has a comprehensive policy framework on violence against women (VAW), implementation has been slow and incomplete in primary healthcare (PHC), and little is known about the implementation challenges. This paper aims to assess the readiness of two PHC clinics in urban Brazil to integrate an intervention to strengthen their DV response. MethodsWe conducted 20 semi-structured interviews with health managers and health providers; a document analysis of VAW and DV policies from São Paulo and Brazil; and 2 structured facility observations. Data were analysed using thematic analysis. ResultsFindings from our readiness assessment revealed gaps in both current policy and practice needing to be addressed, particularly with regards to governance and leadership, health service organisation and health workforce. DV received less political recognition, being perceived as a lower priority compared to other health issues. Lack of clear guidance from the central and municipal levels emerged as a crucial factor that weakened DV policy implementation both by providers and managers. Furthermore, responses to DV lost visibility, as they were diluted within generic violence responses. The organizational structure of the PHC system in São Paulo, which prioritised the number of consultations and household visits as the main performance indicators, was an additional difficulty in legitimising healthcare providers' time to address DV. Individual-level challenges reported by providers included lack of time and knowledge of how to respond, as well as fears of dealing with DV. ConclusionAssessing readiness is critical because it helps to evaluate what services and infrastructure are already in place, also identifying obstacles that may hinder adaptation and integration of an intervention to strengthen the response to DV before implementation.